Testing the validity of academic staff performance predictors and their effects on workforce performance - Mohammed Borhandden Musah; Lokman Mohd Tahir; Hairuddin Mohd Ali; Shafeeq Vazhathodi Hussain Al-Hudawi; Mohammad Issah; Adnan Mohammed Farah; Asma Khaleel Abdallah; Naail Mohammed Kamil (Institute of Advanced Engineering and Science, 2023)
This study investigated the validity of quality culture (QC) and excellent work culture (EWC) constructs, and their effects on academic staff performance (ASP) mediated by EWC in selected West Malaysian higher education institutions (HEIs). The study included 1,068 faculty members from eight HEIs. The findings showed that QC construct is represented by nine separate elements, whereas two factors index both ASP and EWC. Moreover, the findings established evidence of construct reliability and validity in relation to the elements comprised the three constructs. The findings indicated that quality culture and excellent work culture have direct impact on ASP. The findings also showed that excellent work culture exhibits indirect causal effect on academic staff performance. This empirical study analyzed the mediating effect of EWC on ASP, which has not been extensively examined in the context of Malaysian HEIs.